2021
DOI: 10.1039/d1tb01141c
|View full text |Cite
|
Sign up to set email alerts
|

RNA BioMolecular Electronics: towards new tools for biophysics and biomedicine

Abstract: Nanoscience has enabled the electrical study of individual biomolecules. This perspective presents the nascent field of RNA BioMolecular Electronics, overviewing the main developments and exploring recent and future potential applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 110 publications
(148 reference statements)
1
10
0
Order By: Relevance
“…With unique structural and self-assembly properties [ 86 , 87 , 88 ], they have also been widely studied in biological functions and biotechnological applications. Since the inventions of break junction techniques, the electrical properties of oligonucleotides, including DNA [ 89 , 90 ], RNA [ 91 ] and RNA: DNA Hybrids [ 92 ], have been explored in the molecular junctions. It was found that the single-molecule conductance of these oligonucleotides is very sensitive to the molecular length [ 93 ], the helical conformation [ 94 ], the base sequence [ 95 ], and the environmental surroundings [ 96 ].…”
Section: Genetic Materials Detectionmentioning
confidence: 99%
“…With unique structural and self-assembly properties [ 86 , 87 , 88 ], they have also been widely studied in biological functions and biotechnological applications. Since the inventions of break junction techniques, the electrical properties of oligonucleotides, including DNA [ 89 , 90 ], RNA [ 91 ] and RNA: DNA Hybrids [ 92 ], have been explored in the molecular junctions. It was found that the single-molecule conductance of these oligonucleotides is very sensitive to the molecular length [ 93 ], the helical conformation [ 94 ], the base sequence [ 95 ], and the environmental surroundings [ 96 ].…”
Section: Genetic Materials Detectionmentioning
confidence: 99%
“…Biomolecular electronics, also named molecular bioelectronics, has been an emerging multidisciplinary field at the leading edge between biology, chemistry, materials, nanoscience, and engineering. [1][2][3][4] It mainly moves toward the integration of various types of biomolecules (such as nucleic acids, proteins, peptides, or amino acids) as active electronic elements, with the aim of either building new functional bioelectronic devices or deepening the understanding of the fundamental biological processes in life. [5][6][7][8][9] Ever since Luigi Galvani discovered 'animal electricity' in the 1780s, 10 research in this field has been rapidly expanding and branching out into many interdisciplinary applications, including biosensors (for clinical, environmental, and food analysis), 6,8,9 biocomputers (for information storage and processing devices) 11,12 and biofuel cells (for energy conversion from raw biomass to electricity).…”
Section: Introductionmentioning
confidence: 99%
“…16,[23][24][25][26] This has led to a myriad of theoretical and experimental studies of the electronic properties of individual protein molecules and their assimilation as active components in electronic circuits, sparking interest in the past decades and giving rise to a new field of protein-based bioelectronics, also referred to as ''proteotronics''. 3,[15][16][17][18][19]26,27 In general, protein-based bioelectronic devices rely on capturing single proteins or their monolayer onto different configurations of electrodes and exploring the electronic conductivity by measuring the current response of devices as a function of bias voltage. Nano-gapped electrodes or tunnelling devices, typically containing a pair of electrodes with nanosized gaps, are commonly used for constructing the protein devices.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Scanning Tunneling Microscopic (STM)-assisted break junctions method (STM-BJ) 10 has recently allowed the first single-molecule detection and identification of RNA from E. coli strains 11 , between several other single-molecule electrical studies on oligonucleotides [12][13][14][15][16][17] . This indicates that the same approach could be used for cancer biomarker RNA sequences from human origin 18 , more specifically, ctNAs could be targeted by their corresponding mutations that are biomarkers associated with cancer risk. These biomarkers could be detected by designing DNA probes complementary to the target sequence and modified with chemical groups that allow binding to electrodes (i.e., thiol binding groups; see Fig.…”
mentioning
confidence: 99%
“…1. Detection of cancer biomarkers using the STM-BJ single-molecule conductance approach 18 . a, Liquid biopsy samples contain circulating nucleic acids that can be detected with a complementary DNA probe capable of binding to STM electrodes.…”
mentioning
confidence: 99%